The effect of training and experience on mass casualty incident triage performance: Evidence from emergency personnel in a high complexity university hospital (2019)
Mass casualty incident (MCI) can occur at any time and place and health care institutions must be prepared to deal with these incidents. Emergency department staff rarely learn how to triage MCI patients during their medical or nurse degrees, or through on-the-job training. This study aims to evaluate the effect of training and experience on the MCI triage performance of emergency personnel. METHODOLOGY: This was a cross-sectional prospective study that analyzed the performance of 94 emergency department staff on the triage classifications of 50 trauma patients, before and after a short training in MCI triage, while taking into account their academic background and work experience. RESULTS: The participants were assigned initially to one of two groups: low experience if they had less than 5 years of practice, and high experience if they had more than 5 years of practice. In the low experience group, the initial accuracy was 45.76 percent, over triage 45.84 percent, and subtriage 8.38 percent. In the high experience group, the initial accuracy was 53.80 percent, over triage 37.66 percent, and sub triage 8.57 percent. POSTINTERVENTION RESULTS: In the low experience group, the post intervention accuracy was 63.57 percent, over triage 21.15 percent, and subtriage 15.30 percentage. In the high experience group, the postintervention accuracy was 67.66 percentage, over triage 15.19 percentage, and subtriage 17.14 percentage. CONCLUSION: Upon completion of this study, it can be concluded that MCI triage training significantly improved the performance of all those involved in the workshop and that experience plays an important role in MCI triage performance.